Comparison of Acceptance Commitment Therapy (ACT) and Cognitive Behavioral Therapy (CBT) in Reducing Depression symptoms and Increasing Happiness of Iranian adolescent Girl Students (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
This study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Cognitive-Behavioral Therapy (CBT) in reducing depression symptoms and increasing happiness of Iranian adolescent girls in Shiraz-Iran in 2017-2018 educational year. The research method was quasi- Experimental with assessing participants with pre -Test, Post-Test plans and control group. The Statistical population of this study consisted of 45 adolescent girl Students- between 13-17 years old - who were referred to the school’s student counselling centres because of their poor mental well being. They were selected by convenient sampling method and then they were randomly divided into three groups of 15 participants (two experimental groups and one control group). The Depression and Happiness variables were assessed by using Beck’s Depression Inventory (1996) and the Oxford Happiness Questionnaire (1989) respectively.Commitment Therapy Package was implemented for 8 sessions and Cognitive-Behavioral Package was implemented for 10 sessions for each Experimental groups separately. The Data were analysed by using SPSS24 software and analysis of multivariate covariance (MANCOVA). The results of this study suggested that both ACT and CBT Therapy approach had an acceptable effect on reducing Depression and increasing Happiness in Adolescent girls (p